How Comparable are Microbial Electrochemical Systems around the Globe? An Electrochemical and Microbiological Cross‐Laboratory Study. Issue 11 (18th May 2021) - Santoro, Carlo; Babanova, Sofia; Cristiani, Pierangela; Artyushkova, Kateryna; Atanassov, Plamen; Bergel, Alain; Bretschger, Orianna; Brown, Robert K.; Carpenter, Kayla; Colombo, Alessandra; Cortese, Rachel; Erable, Benjamin; et al.
Abstract: Invited for this month′s cover is the collaborative work among Univ. of Milano‐Bicocca, Ricerca sul Sistema Energetico S.p.A., Univ. degli Studi di Milano, Univ. of California Irvine, Univ. of New Mexico, CNRS Toulouse. Technische Univ. Braunschweig, Aquacycl LLC, J. Craig Venter Institute, Helmholtz‐Centre for Environmental Research. The image shows a sketch of a microbial fuel cell and a target indicating the need of developing common standards for the field of microbial electrochemical technologies. The Full Paper itself is available at 10.1002/cssc.202100294 . Abstract : "The scope of the work was to target similar results when using identical setups and protocols around the globe…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.202100294 . View the Front Cover here: 10.1002/cssc.202100825 .